An unusual case of multiple gastrointestinal stromal tumors in the small bowel presenting as occult and overt gastrointestinal bleeding. Issue 7 (22nd July 2022) - Yeaman, Fiona; Abasszade, Joshua; Varma, Poornima; Swan, Michael
Abstract: We present a case report of a 59‐year‐old woman with multiple gastrointestinal stromal tumors as a cause of gastrointestinal bleeding. She initially presented with recurrent iron deficiency anemia and subsequent gastrointestinal bleeding over 10 years. An initial angiodysplastic lesion was identified, treated, and spot tattooed. Recurrent symptoms occurred leading to repeat investigations with a further subepithelial lesion with ulceration being identified. Computerized tomography enterography subsequently revealed an ileal intraluminal enhancing lesion, and she was referred to surgery. Surgical resection was ultimately performed, and multiple lesions were found to be present with histology revealing multiple gastrointestinal stromal tumors. Abstract : Gastrointestinal stromal tumors (GIST) are often single tumors whereas multiple GISTs are usually associated with familial syndromes. Sporadic multiple GISTs are rarely reported, and this case demonstrates an unusual situation of multiple GISTs causing iron‐deficiency anemia, highlighting the importance of obtaining both radiological and direct imaging to aid diagnosis.